Seletividade de herbicidas aplicados em pré e pós-emergência em feijão-caupi na savana de Roraima - Cruz, Anna Bárbara de Souza (2015)
The objective of this study was to evaluate the selectivity and efficiency of herbicides applied in pre and post-emergence in cv. BRS Aracê cowpea. Two experiments were carried, with application of herbicides in pre-emergence and the other with post-emergence application in a randomized block design. There were 10 treatments for each of the experiments, which were performed 4 intoxication visual assessments with 7 days interval between them. Pre-emergence herbicides were tested the metribuzin, sulfentrazone, S-metolachlor, pendimethalin, oxadiazon, alachlor, metribuzin + pendimethalin, metribuzin + alachlor. Since post-emergence were tested quizalofop-p-ethyl, bentazon, fomesafen, imazethapyr, imazamox, quizalofop-p-ethyl + imazamox, quizalofop-p-ethyl + imazethapyr, quizalofop-p-ethyl + bentazon and two controls in each of the experiments, one with and one without weeding weeding. The metribuzin herbicide and all its mixtures are not recommended pre-emergence in the cowpea crop because there were not selective to this crop, reducing the total germination of cowpea seed when applied alone, and when mixed with other herbicide caused extremely strong intoxication. The oxadiazon herbicides, pre-emergence, and quizalofop-p-ethyl + imazamox, post-emergence were considered selective for cowpea in Roraima, due to the low toxicity of the plants in the field and high productivity. Keywords: Chemical control, Weed, Vigna unguiculata.